Abordagem CTS e a alfabetização científica: implicações para as diretrizes do programa ciência na escola - Gomes, Orleylson Cunha (2015)
The scientific and technological literacy emerges in the educational context with the development of the STS movement, based on the idea of allowing citizens to participate in discussions on the conduct of science and technology in society. The practice is widely supported by those who aim at the formation of autonomous individuals with the basic domain of scientific and ethical knowledge; they can participate in decisions involving the state and the S & T policies. In this sense, our research has focused on understanding how the Science Program in schooling PCE contributes to the formation of students scientifically literate, from projects developed in Manaus city schools in 2014. To do this we divided the work in two stages, the first characterized by the application of VOSTS questionnaire (Aikenhead, 1992) and the bibliographic research. The second stage was based on content analysis of scientific technical reporting (Bardin, 1977) and of the objectives proposed in the works selected in the light of the ideas advocated in Bloom's Taxonomy (2001). We also conduct the questionnaire application with open questions to the teachers who participated in the PCE and have had their projects selected for analyzes of this work with a view to know their views on the CTS interaction. The results allows us to show that possibly the projects developed in schools turn away from the idea of questioning, reflection and critical issues that deserve to be discussed in our view, on Science and Technology, so that they may be entering students in the debate on the implications of these two fields of knowledge nowadays. Implications for the PCE proposes to bring students to scientific literacy and thereby develop the ability to participate in scientific and technological development in the regional scenario, we find that the projects develop still laden with traditional assumptions about science, based on the transmission content and demonstration experiments, these activities, which in our view, distance themselves from the ACT assumptions widely disseminated in the educational environment and adopted by our work. However, the Program is believed one of the steps for initiation of students in scientific circles, allowing that develops among the participants the ability to follow the scientific career